A Mixed Reality-Based Platform towards Human-Cyber-Physical Systems with IoT Wearable Device for Occupational Safety and Health Training - Chi Ho Jimmy Li; Vincy Liang; Yuk Ting Hester Chow; Hiu-Yin Ng; Shek-Ping Li (Applied Sciences, 2022)
Occupational safety and health (OSH) should be regarded as a crucial challenge that affects the public world widely. Work-related accidents and occupational illness contribute to considerable mortality and morbidity. As technology advances, mixed reality (MR) has gained popularity. To minimize occupational accidents occurring in the workplace and reduce human training time, an MR-based platform for OSH training combined with CPS and IoT technology is proposed in this paper. Multi-criteria decision-making (MCDM) and fuzzy-analytic hierarchy process (FAHP) were applied to evaluate and select suitable gloves. Only when the MR wearable devices are improved can a more powerful MR-based OSH training program be established. A higher immersive level of OSH training offers people a more realistic experience. They will better understand possible risks in workers’ future work, resulting in a lower occupational accident rate in the workplace.